Comparison of neostigmine and sugammadex for hemodynamic parameters in neurointerventional anesthesia - Tsai, Yu-Hsun; Chen, Chun-Yu; Wong, Ho-Fai; Chou, An-Hsun (Frontiers in Neurology, 2023)
Introduction Hemodynamic stability is important during neurointerventional procedures. However, ICP or blood pressure may increase due to endotracheal extubation. The aim of this study was to compare the hemodynamic effects of sugammadex and neostigmine with atropine in neurointerventional procedures during emergence from anesthesia. Methods Patients undergoing neurointerventional procedures were allocated to the sugammadex group (Group S) and the neostigmine group (Group N). Group S was administered IV 2 mg/kg sugammadex when a train-of-four (TOF) count of 2 was present, and Group N was administered neostigmine 50 mcg/kg with atropine 0.2 mg/kg at a TOF count of 2. We recorded heart rate, systolic blood pressure, diastolic blood pressure, mean blood pressure (MAP), and peripheral arterial oxygen saturation during administration of the reverse agent and at 2, 5, 10, 15, 30, 120 min, and 24 h thereafter. The primary outcome was blood pressure and heart rate change after the reversal agent was given. The secondary outcomes were systolic blood pressure variability standard deviation (a measure of the amount of variation or dispersion of a set of values), systolic blood pressure variability-successive variation (square root of the average squared difference between successive blood pressure measurements), nicardipine use, time-to-TOF ratio ≥0.9 after the administration of reversal agent, and time from the administration of the reversal agent to tracheal extubation. Results A total of 31 patients were randomized to sugammadex, and 30 patients were randomized to neostigmine. Except for anesthesia time, there were no significant differences in any of the clinical characteristics between the two groups. The results demonstrated that the increase in MAP from period A to B was significantly greater in Group N than in Group S (regression coefficient = −10, 95% confidence interval = −17.3 to −2.7, P = 0.007). The MAP level was significantly increased from period A to B in the neostigmine group (95.1 vs. 102.4 mm Hg, P = 0.015), but it was not altered in Group S. In contrast, the change in HR from periods A to B was not significantly different between groups. Conclusion We suggest that sugammadex is a better option than neostigmine in interventional neuroradiological procedures due to the shorter extubation time and more stable hemodynamic change during emergence.